The interaction of serum testosterone levels and androgen receptor CAG repeat polymorphism on the risk of erectile dysfunction in aging Taiwanese men. (27th July 2015) - Liu, C.‐C.; Lee, Y.‐C.; Tsai, V.F.S.; Cheng, K.‐H.; Wu, W.‐J.; Bao, B.‐Y.; Huang, C.‐N.; Yeh, H.‐C.; Tsai, C.‐C.; Wang, C.‐J.; Huang, S.‐P.
Abstract Testosterone has been found to play important roles in men's sexual function. However, the effects of testosterone can be modulated by androgen receptor (AR) CAG repeat polymorphism. It could also contribute to the risk of erectile dysfunction (ED). The aim of this study is to evaluate the interaction of serum testosterone levels and AR CAG repeat polymorphism on the risk of ED in aging Taiwanese men. This cross‐sectional data of Taiwanese men older than 40 years were collected from a free health screening held between August 2010 and August 2011 in Kaohsiung city, Taiwan. All participants completed a health questionnaires included five‐item version of the International Index of Erectile Function (IIEF‐5) and the International Prostate Symptoms Score, received a detailed physical examination and provided 20 cm3 whole blood samples for biochemical and genetic evaluation. The IIEF‐5 was used to evaluate ED. Serum albumin, total testosterone (TT), and sex hormone‐binding globulin levels were measured. Free testosterone level was calculated. AR gene CAG repeat polymorphism was determined by direct sequencing. Finally, 478 men with the mean age of 55.7 ± 4.8 years were included. When TT levels were above 330 ng/dL, the effect of testosterone level on erectile function seemed to reach a plateau and a significantly negative correlation between AR CAG repeat length and the score of IIEF‐5 was found (r = −0.119, p = 0.034). After adjusting for other covariates, the longer AR CAG repeat length was still an independent risk factor for ED in subjects with TT above 330 ng/dL (p = 0.006), but not in TT of 330 ng/dL or below. In conclusion, both serum testosterone levels and AR CAG repeat polymorphism can influence erectile function concomitantly. In subjects with normal TT concentration, those with longer AR CAG repeat lengths have a higher risk of developing ED.